Departmental distribution and clinical epidemiology of acute kidney injury in hospitalized elders - Xing-yang Zhao; Gang Xu; Shu-wang Ge (Editorial Department of Journal of Clinical Nephrology, 2024)
Objective To explore the distribution, incidence, clinical characteristics, and in-hospital mortality risk factors associated with acute kidney injury （AKI） in hospitalized elders across various clinical departments. Method A retrospective analysis was conducted for medical records of elders aged ≥65 years admitted between January 1, 2018, and December 31, 2022. Collected clinical data included demographic profiles, comorbidities, medication usage and laboratory test results. AKI was defined based upon the dynamic baseline creatinine algorithm according to the guidelines of the Kidney Disease:Improving Global Outcomes. Stacked bar charts were employed for displaying the distribution and incidence of AKI across different departments. Univariate and multivariate Logistic regression analyses were performed for examining various risk factors for in-hospital mortality. Kaplan-Meier survival curve and Log-rank test were employed for comparing cumulative survival rates among elders of varying AKI stages. Results A total of 154,696 elder episodes fulfilled the inclusion criteria and 6,879（4.4%） developed AKI. Significant differences existed in the distribution and incidence of AKI across departments. The highest incidence was in Intensive Care Unit at 30.1%, followed by Cardiovascular Surgery at 24.3% and Trauma Surgery at 11.3%. The in-hospital mortality rate of AKI elders was 15.9% and it spiked with AKI severity. Multivariate Logistic regression analysis revealed that higher AKI stages （OR = 2.89, 95%CI: 2.15-3.88, P＜0.001）, pulmonary infection （OR = 2.01, 95%CI: 1.59-2.56, P＜0.001）, malignancy（OR = 1.59, 95%CI: 1.25-2.04, P＜0.001） and hypoalbuminemia （OR = 1.94, 95%CI: 1.54-2.43, P＜0.001） were independent risk factors for in-hospital mortality. Only 6.0% of AKI elders had an "AKI" diagnosis at discharge. Conclusion The incidence of AKI in elders rises with age. AKI elders often have underlying diseases and receive nephrotoxic medications, predominantly at clinical departments other than nephrology. Age, AKI stage, pulmonary infection, DM, malignancy and hypoalbuminemia are risk factors for in-hospital mortality in AKI elders. A large majority of AKIs are underdiagnosed during hospitalization, highlighting the need for heightened attention to AKI elders.